Cellular Performance Comparison of Biomimetic Calcium Phosphate Coating and Alkaline-Treated Titanium Surface. (12th December 2013) - Yu, Xiaohua; Wei, Mei
Abstract : The influence of biomimetic calcium phosphate coating on osteoblasts behavior in vitro is not well established yet. In this study, we investigated the behavior of osteoblastic rat osteosarcoma 17/2.8 cells (ROS17/2.8) on two groups of biomaterial surfaces: alkaline-treated titanium surface (ATT) and biomimetic calcium phosphate coated ATT (CaP). The cell attachment, proliferation, differentiation, and morphology on these surfaces were extensively evaluated to reveal the impact of substrate surface on osteoblastic cell responses. It was found that the ROS17/2.8 cells cultured on the ATT surface had higher attachment and proliferation rates compared to those on the CaP surface. Our results also showed that the calcium phosphate coatings generated in this work have an inhibiting effect on osteoblast adhesion and further influenced the proliferation and differentiation of osteoblast compared to the ATT surface in vitro . Cells on the ATT surface also exhibited a higher alkaline phosphatase activity than on the CaP surface after two weeks of culture. Immunofluorescence staining and scanning electron microscopy results showed that the cells adhered and spread faster on the ATT surface than on the CaP surface. These results collectively suggested that substrate surface properties directly influence cell adhesion on different biomaterials, which would result in further influence on the cell proliferation and differentiation.